1994
DOI: 10.1055/s-2008-1071574
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Antibodies in Cerebrovascular Ischemia and Stroke in Childhood

Abstract: We report on eight children who suffered from cerebrovascular ischemia or stroke at the age of 2 or up to 11 years. Antiphospholipid antibodies (APLA) were detected in two cases during the ischemic event and in six cases during follow-up examinations (after six weeks or within a span of six years). In two patients multiple stenoses of basal cerebral arteries were found; one of them suffered from moyamoya syndrome. The acute hemiplegia in one patient was linked to an asymptomatic mycoplasmal infection and APLA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 30 publications
1
20
0
1
Order By: Relevance
“…An underlying autoimmune condition, as described in Down's syndrome, inducing the appearance of these antibodies and a progressive vascular damage, could not be discarded. 21 Variable frequency of prothrombotic disorders has been reported in non-MMS children with AIS 17,37,38,53 ; in our previous study, we found these abnormalities in 7 of the 30 children (23%) evaluated. 39 Few reports have described the probable relationship between hemostatic abnormalities and MMS.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…An underlying autoimmune condition, as described in Down's syndrome, inducing the appearance of these antibodies and a progressive vascular damage, could not be discarded. 21 Variable frequency of prothrombotic disorders has been reported in non-MMS children with AIS 17,37,38,53 ; in our previous study, we found these abnormalities in 7 of the 30 children (23%) evaluated. 39 Few reports have described the probable relationship between hemostatic abnormalities and MMS.…”
Section: Discussionmentioning
confidence: 96%
“…39 Few reports have described the probable relationship between hemostatic abnormalities and MMS. [15][16][17][18][19][20][21][22][23][24][25] In our series, a prothrombotic disorder was detected in 4 of our patients (40%). Inherited protein S deficiency was detected in 1 patient, and persistent positive LA or ACA was found for months or even years in the remaining 3 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moderate elevations of aCL antibodies have been associated with thrombotic events in 10 of 13, 3 of 4 and 4 of 4 children and 9 of 35 adults with APS [3, 6, 7, 8]. Nevertheless, in population studies, the risk of thrombosis increases at levels >38 or 40 GPL units [9, 10].…”
Section: Discussionmentioning
confidence: 99%
“…13,56,64,72) However, these studies have indirectly proved the correlation between abnormalities of the immune system and moyamoya disease. Indeed, it is conceivable that the true genetic triggers of moyamoya disease are close to the abnormalities seen in HLA alleles disclosed.…”
Section: Proteomicsmentioning
confidence: 99%